1998
DOI: 10.1088/0965-0393/6/6/006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and simulation of beryllium diffusion in InGaAs compounds grown by gas source molecular beam epitaxy

Abstract: The diffusion of Be during post-growth rapid thermal annealing (RTA) in InGaAs layers grown by gas source molecular beam epitaxy (GSMBE) has been studied. The observed secondary ion mass spectrometry (SIMS) concentration distributions, obtained for annealing cycles with time durations of 10 s to 240 s and temperatures in the range for Be doping concentration of , could be explained by a kick-out mechanism considering neutral Be interstitials and singly positively charged group III self-interstitials. Be and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To obtain quantitative data fits, two kick-out models of the substitutional-interstitial diffusion (SID) mechanism were considered. The two models are based on the neutral Be interstitial species Be 0 i and the singly positively charged In, Ga self-interstitials I + III in In 0.53 Ga 0.47 As [3]; however, in InP the first model involves the singly positively charged Be interstitial species Be + i [1] with the doubly positively charged In self-interstitials I 2+ III and the second model uses, as in In 0.53 Ga 0.47 As, the neutral Be interstitial species Be 0 i with the singly positively charged In self-interstitials I + III , according to the following diffusion reaction:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain quantitative data fits, two kick-out models of the substitutional-interstitial diffusion (SID) mechanism were considered. The two models are based on the neutral Be interstitial species Be 0 i and the singly positively charged In, Ga self-interstitials I + III in In 0.53 Ga 0.47 As [3]; however, in InP the first model involves the singly positively charged Be interstitial species Be + i [1] with the doubly positively charged In self-interstitials I 2+ III and the second model uses, as in In 0.53 Ga 0.47 As, the neutral Be interstitial species Be 0 i with the singly positively charged In self-interstitials I + III , according to the following diffusion reaction:…”
Section: Resultsmentioning
confidence: 99%
“…The diffusion differential equations for Be and group III mobile species, including the Fermi-level effect, the electric field produced by the charge distribution and the bulk selfinterstitial generation/annihilation, for each model, were solved numerically, using the explicit finite-difference method [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was commonly agreed that a local thermodynamic equilibrium held between a substitutionally dissolved beryllium, self-interstitials III I q+ and interstitial beryllium atoms i Be r + [1,[7][8][9][11][12][13][14]. Yoshida et al [15] carried out a qualitative consideration of the kick-out mechanism and found that there was no essential difference between the macroscopic description of impurity diffusion by means of the kick-out mechanism and the mechanism of formation, migration, and dissociation of the pairs "impurity atomself-interstitial".…”
Section: Imentioning
confidence: 99%